Makna Filosofis Motif Batik sebagai Identitas Budaya Masyarakat Lebak - Anisa Kapeanis; Daroe Iswatiningsih Iswatiningsih; Siti Afifatur Rohmah; Paramita Candra Dewi (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
Lebak Batik is a cultural heritage with high philosophical value and is closely related to the life of the Baduy people in Lebak Regency, Banten. This study aims to describe the stages of making Lebak Batik and examine the philosophical meaning of its motifs. The research method used is a qualitative descriptive approach with data collection techniques through direct observation, interviews with craftsmen and cultural figures, and literature studies. The study results show that the making of Lebak Batik still maintains traditional techniques with the main stages, including pattern making, waxing, natural coloring, wax removal, and fabric refinement. The motifs in Lebak Batik have strong philosophical meanings, such as Leuit Baduy, which symbolizes food security; Kaso Rancak, which reflects mutual cooperation; and Seren Taun, which symbolizes gratitude for the harvest.